PENENTUAN FLUID VELOCITY DAN FLOW RATE SUMUR LHD-SY, WILAYAH KERJA PANAS BUMI LAHENDONG BERDASARKAN SURVEI PTS LOGGING - Fatma, Fatma; Johanis, Sheehan; Rohani, Adelia (Sekolah Tinggi Teknologi MIGAS, 2024)
The “LHD-SY” Geothermal Field is a production well located at “KR” Cluster of PT. Pertamina Geothermal Energy in Lahendong Working Area. In order to determine the characteristics of a geothermal well that can produce optimally, the well is tested using the PTS Logging survey method. The analysis is carried out by calibrating the spinner data to be converted into fluid velocity and flow rate. This data later can be used to determine the potential and productivity of geothermal wells. From the calculation results, the average fluid velocity values sequentially for depths of 1,100, 1,318, 1,472 and 1,600 mMD are 1682.90, 1531.98, 1337.00 and 879.91 m/min, and the flow rate is 86.13. 78.40, 68.43, and 45.03 m3/min.